Performance and Ageing Robustness of Graphite/NMC Pouch Prototypes Manufactured through Eco‐Friendly Materials and Processes. Issue 18 (23rd August 2017) - Loeffler, Nicholas; Kim, Guk.‐T.; Passerini, Stefano; Gutierrez, Cesar; Cendoya, Iosu; De Meatza, Iratxe; Alessandrini, Fabrizio; Appetecchi, Giovanni B.
Abstract: Graphite/lithium nickel‐manganese‐cobalt oxide (NMC), stacked pouch cells with nominal capacity of 15–18 Ah were designed, developed, and manufactured for automotive applications in the frame of the European Project GREENLION. A natural, water‐soluble material was used as the main electrode binder, thus allowing the employment of H2 O as the only processing solvent. The electrode formulations were developed, optimized, and upscaled for cell manufacturing. Prolonged cycling and ageing tests revealed excellent capacity retention and robustness toward degradation phenomena. For instance, above 99 % of the initial capacity is retained upon 500 full charge/discharge cycles, corresponding to a fading of 0.004 % per cycle, and about 80 % of the initial capacity is delivered after 8 months ageing at 45 °C. The stacked soft‐packaged cells have shown very reproducible characteristics and performance, reflecting the goodness of design and manufacturing. Abstract : Eco‐batteries : Graphite/lithium nickel‐manganese‐cobalt oxide, stacked pouch cells with nominal capacity of 15–18 Ah are designed, developed, and manufactured for automotive applications using a natural, water‐soluble material as the main electrode binder, thus allowing the employment of H2 O as the only processing solvent.